Hepatitis B virus infections in apparently healthy urban Nigerians: data from pre-vaccination tests - Adoga, Moses P.; Gyar, Silas D.; Pechulano, Simon; Bashayi, Obadiah D.; Emiasegen, Samuel E.; Zungwe, Timothy; Iperepolu, Odunayo H.; Agupugo, Chinwe; Agwale, Simon M. (The Journal of Infection in Developing Countries, 2010)
Background: In spite of the availability of an effective vaccine since 1982 against hepatitis B, infection with hepatitis B virus (HBV), which is 50 to 100 times more infectious than HIV, still persists in most parts of the world with Nigeria being described as an endemic zone. We therefore set out to establish the prevalence of this infection and evaluate its relationship with age and gender in urban Nigerians. Methodology: During pre-vaccination tests, blood samples were collected by finger-prick and venepuncture from 1,891 subjects aged ≤ 60 years, between 2008 and 2009 after having obtained informed consent and ethical clearance. Smart Check HBsAg (Globalemed, Cape Town, South Africa) and ShantestTM-HBsAg Elisa (Shantha Biotechnics Ltd, Hyderabad, India) were used for initial and confirmatory tests respectively. Results: Of the 1,891 participants, 957 (50.6 %) were males and 934 (49.4%) were females. Overall 114 (6.0%) were positive, of whom 71 (7.4%) were males and 43 (4.6%) females. Those aged 21-30 years had the highest infection rate, and males were more likely to be infected with the virus than females (P > 0.05). Conclusions: Such a high prevalence of a vaccine-preventable infection questions the effectiveness of the Nigerian vaccination strategies. The Nigerian government hepatitis B vaccination programme, which hitherto is limited to the National Childhood Immunisation Programme, should include the adult population.